The Incorporation of Hemin Catalysts and Alumina Nanoparticles in a Medium of Spondias mombin Leaf Extract of A Sulfonated Polysulfone-Polyaniline_Alumina Membrane Electrode Assembly for Fuel Cell Technologies - Armi Wulanawati; Yoki Yulizar; Sri Mulijani; Fadli Rohman (Masyarakat Katalis Indonesia - Indonesian Catalyst Society (MKICS), 2026)
The development of sustainable Membrane Electrode Assembly (MEA) is crucial for advancing fuel cell technology. This study presents a novel MEA design that incorporates metal oxide nanoparticles synthesized using natural materials into a high-performance membrane and employs a non-platinum catalyst. Specifically, alumina (Al2O3) nanoparticles were synthesized in medium Spondias mombin leaf extract, which served as both a base source and a capping agent. Alumina nanoparticles combined with polyaniline serve as a composite material to enhance the hydrophilicity, structural and thermal stability, power density, and proton conductivity of a sulfonated polysulfone-based composite membrane. Alumina is known as a catalyst support with a large surface area, while polyaniline is a conductive polymer that readily interacts with metal oxides and hemin, which is rich in electrons, exhibits catalytic activity. Based on the characterization of physical and chemical properties, the SPSU-PANI_Al2O3 7.5% composite MEA using a hemin catalyst on the cathode in a fuel cell (DMFC) demonstrated good structural and thermal stability, low methanol permeabilitity (3.37×10-6 cm2/s), and high-power density (90.76 mW/cm2), but low proton conductivity. Furthermore, Electrochemical cell testing of the hemin catalyst, which identified two reduction peaks at 0.48-0.52 V and 1.22 V similar to those of the Pt catalyst at the cathode demonstrates that the hemin catalyst provides comparable cell potential and catalytic activity for the oxygen reduction reaction for fuel cell technologies. Copyright © 2026 by Authors, Published by BCREC Publishing Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).